Respuesta :
Answer:
Step-by-step explanation:
basically here we wanna get y by itself
so
2x + 3y = -1
subtract 2x from both sides
3y = -2x -1
then to get y by itself we have to divide everything by 3
y = -2/3x - 1/3
this is your equation in slope intercept form
hope this helps <3
Answer: y= -2/3 x -1/3
Explanation:
3y= -2x-1 (subtract 2x from 3y and transfer it to the other side)
y= -2x/3 -1/3 (divide 3 on both sides to leave y alone)
Final Answer: y= -2/3 x -1/3 (y equals to negative two-third x minus one-third)
Explanation:
3y= -2x-1 (subtract 2x from 3y and transfer it to the other side)
y= -2x/3 -1/3 (divide 3 on both sides to leave y alone)
Final Answer: y= -2/3 x -1/3 (y equals to negative two-third x minus one-third)